A cell cycle timer for asymmetric spindle positioning. - Erin K McCarthy Campbell; Adam D Werts; Bob Goldstein (PLoS Biology)
The displacement of the mitotic spindle to one side of a cell is important for many cells to divide unequally. While recent progress has begun to unveil some of the molecular mechanisms of mitotic spindle displacement, far less is known about how spindle displacement is precisely timed. A conserved mitotic progression mechanism is known to time events in dividing cells, although this has never been linked to spindle displacement. This mechanism involves the anaphase-promoting complex (APC), its activator Cdc20/Fizzy, its degradation target cyclin, and cyclin-dependent kinase (CDK). Here we show that these components comprise a previously unrecognized timer for spindle displacement. In the Caenorhabditis elegans zygote, mitotic spindle displacement begins at a precise time, soon after chromosomes congress to the metaphase plate. We found that reducing the function of the proteasome, the APC, or Cdc20/Fizzy delayed spindle displacement. Conversely, inactivating CDK in prometaphase caused the spindle to displace early. The consequence of experimentally unlinking spindle displacement from this timing mechanism was the premature displacement of incompletely assembled components of the mitotic spindle. We conclude that in this system, asymmetric positioning of the mitotic spindle is normally delayed for a short time until the APC inactivates CDK, and that this delay ensures that the spindle does not begin to move until it is fully assembled. To our knowledge, this is the first demonstration that mitotic progression times spindle displacement in the asymmetric division of an animal cell. We speculate that this link between the cell cycle and asymmetric cell division might be evolutionarily conserved, because the mitotic spindle is displaced at a similar stage of mitosis during asymmetric cell divisions in diverse systems.